Linear and nonlinear chromatic integration in the mouse retina - Mohammad Hossein Khani (Nature Portfolio, 2021)
This study shows that ganglion cells in mouse retina integrate chromatic visual signals either linearly or nonlinearly. Nonlinear chromatic integration depends on rod photoreceptor activity and on surround inhibition and may help detect chromatic boundaries, such as the skyline in natural scenes.